Challenges and Opportunities for Improving Household Sanitation in the Ger Areas of Ulaanbaatar - Leblanc, Maryanne (World Bank, Washington, DC, 2018)
This report will assist decision makers and other stakeholders in Ulaanbaatar in deciding how to improve sanitation in the Ger areas, which are fast-growing, largely unplanned peri-urban settlements around the city. It is part of a larger study on improving sanitation in cold regions where sewerage may not be a practical solution. The report grew out of a pilot project meant to improve sanitation in the Ger areas by connecting households to the municipal water supply system and to a small, independent sewerage system. For a number of reasons, operating the system was very challenging. Thus, the question arose of what practicable, affordable technical options exist for improving sanitation in the Ger areas of Ulaanbaatar and other cold regions. The study is aimed at answering that question.